AN ANALYSIS OF MORAL VALUE IN MIRACLE IN CELL NO.7 MOVIE - Ema Rohmatul Fazriyah (Universitas Mathla'ul Anwar Banten, 2024)
Movie is one of entertainment media which is interesting for all generation. It contains cultural element, moral message, educations, lifestyles, politics, and history. This research entitles An Analysis of Moral Value in ‘Miracle in Cell No 7’Movie. This research aimed to find out the Moral Value in the subtitles presented in Miracle in cell No 7 movie and describe the way of presented the Moral Value. This research used qualitative content analysis. The data were collected by analyzing the dialogues: the researcher watched movie related to moral value theories, read two subtitles (English & Indonesian version), classified, explained, and concluded. The result of the analysis in this study showed that the movie has some of moral value in the movie, such as sacrifice, mutual help, friendly, patient, keeping promises, optimist, love and affection. To conclude, moral value was expected to provide some information and knowledge in analyzing movie that might be useful especially analyzing the moral value in literary works. Each moral was conveyed basic moral of life. It had an effect on the audience directly or indirectly.